ANALYSIS OF THE EFFECT OF SLEEP DURATION AND FATIGUE ON THE PERFORMANCE OF TRAIN DRIVERS IN DRIVING MONOTONOUS ROUTES IN A TRAIN SIMULATOR USING STRUCTURAL EQUATION MODELING (SEM) - Ramadhanty, Azhary
Train accidents are mostly caused by the negligence of the train drivers who operate the train in fatigue, sleepy, and lack of attention condition. These conditions are caused by sleep deprivation before duty. This research aimed to quantify the factor of the sleep duration, fatigue, sleepiness level, and lack of attention on the performance of train drivers while driving in a train simulator with monotonous routes. The performance of train drivers is a latent variable explained by the indicator of speeding (total of speed limit violations), thus the performance is better to the smaller score. Structural Equation Modeling is used to model the quantity of the factors. The result showed that the performance of train drivers is affected by the factors of sleep duration, sleepiness level, attention, and fatigue with the path coefficient of -0.90, 0.38, -0.12, and 0.05, respectively, which means sleep duration is the most influencing factor on the performance of train drivers. These four factors can explain the performance of the driver by 96.2%.